Crescimento e desenvolvimento do pinhão-manso (Jatropha curcas L.) submetido a diferentes níveis de estresse hídrico - Cavalcante, Kelly Jane Correia (2012)
The jatropha (Jatropha curcas L.) is a plant family Euphorbiaceae perennial oilseed, has great potential as a source for biodiesel production. This work aimed to study the effects of water stress on growth and development through biometric measurements and chlorophyll fluorescence. The study was conducted at the State University of Maranhão - UEMA in Sao Luis - MA, with a completely randomized design, propagation by cuttings, consisting of three treatments (T1 - 200 ml, T2 - T3 and 100 ml - 50 ml daily watering) , totaling 45 plants. The biometric evaluations were made from 56 days after striking, began the implementation of treatments. The biometric variables were evaluated: plant height, stem diameter, number of leaves, falling leaves, leaf area, fresh and dry matter. The number of shoots, number of open flowers and fruit number per plant was also evaluated. We also determined the initial fluorescence (F0), maximal fluorescence (Fm) and quantum efficiency of photosystem II (Fv / Fm), nonphotochemical dissipation (qN) and coefficient of non-photochemical dissipation (NPQ) and Paramenters growth (stem diameter, height, leaf area and leaf number) were affected by water stress demonstrating a decrease in growth.